Growth performance of finishing feedlot lambs fed maize silage inoculated with Bacillus subtilis and lactic acid bacteria - Rabelo, C. H. S. [UNESP]; Lara, E. C. [UNESP]; Basso, F. C. [UNESP]; Harter, C. J.; Reis, R. A. [UNESP] (Cambridge Univ Press, 2018)
Whole-crop maize forage was ensiled without inoculant (control), inoculated with Lactobacillus buchneri and L. plantarum at a rate of 1 x 10(5) cfu/g fresh forage per bacterium (LBLP), or inoculated with Bacillus subtilis and L. plantarum at a rate 1 x 10(5) cfu/g fresh forage per bacterium (BSLP) with the goal to investigate the growth performance of finishing feedlot lambs. Thirty Dorper x Santa Ines lambs (29 +/- 3.5 kg initial body weight) were used in the feedlot programme and assigned (n = 10) to one of three diets containing control, LBLP or BSLP silages in a 60:40 forage:concentrate ratio. Inoculation of maize silage did not alter dry matter intake (overall mean = 1.16 kg/day) and average daily gain (overall mean = 0.217 kg/day) of lambs. Consequently, feed efficiency remained unchanged. Inoculation of maize silage did not alter carcass and meat traits of lambs, with the exception of meat colour, wherein yellowness (b*) decreased by feeding LBLP and BSLP diets compared with the untreated diet. Regarding ruminal fermentation, there was an interaction between diets and the interval at which ruminal fluid was sampled for determining total volatile fatty acid concentration, but inoculation yielded no obvious results. In conclusion, the use of diets based on maize silage inoculated with L. plantarum combined with either L. buchneri or B. subtilis did not display relevant effects on growth performance of lambs; this response might be related to the limited impact of these bacterial inoculants on silage composition.
Keywords: Bacillus subtilis; Lactobacillus spp.; maize silage; ruminal fermentation; silage inoculant